Some lesser known silent crickets (Orthoptera: Gryllidae: Euscyrtinae) from the hilly tracts of India - Meena, Ashok Kumar; Swaminathan, Rajamani; Swaminathan, Tatiana (Zootaxa, 2020)
The present paper deals with the revised description of some lesser known silent-slender crickets of Euscyrtinae (Orthoptera: Gryllidae) from the tropical hilly tracts of India. Besides, we describe a new species, Euscyrtus tubus sp. nov., and report the occurrence of Euscyrtodes ogatai (Shiraki, 1930) from India.